Adres gratulacyjny dla dyrektora Gimnazjum Chełmińskiego Wojciecha Łożyńskiego z okazji 50-lecia pracy pedagogicznej. Źródło do dziejów Chełmna z 1881 roku w zbiorach Muzeum Ziemi Chełmińskiej (Tabularium Historiae, 2021)
In 1881, Chełmno witnessed a very important ceremony. The 50th anniversary of work was celebrated by the long-time director of the Chełmno gymnasium, Dr. Wojciech Łożyński (1808‒1884). Thanks to his efforts, the gymnasium achieved a very high academic level, becoming a center of Polish culture in the Prussian partition. He led to the construction of a modern school building and renovation of the school church. Knowing seven languages, he studied literature and ancient philosophy. He received an honorary doctorate from the University of Bonn and an honorary citizenship of Chełmno. Apart from the press coverage, the material trace of the jubilee celebrations is the congratulatory diploma given to the jubilarian by the teachers’ college. The certificate was awarded by a teacher in the Cadet Corps in Chełmno Karl Natter. The document is an important historical and iconographic source for the history of the city and education. This diploma was presented by Dr. Jerzy Szews in 1987 at the request of the Łożyński family to the collection of the Chełmno Land Museum in Chełmno.